Rowinataworu Luhchi Yoroni = Tunica language textbook (Indiana University Press, 2023)
"The essential guide for learning the Tunica language. For many years, the Tunica-Biloxi Tribe of Louisiana collaborated with students and faculty at Tulane University on a project to revitalize the Tunica language. Tunica had not been spoken or used regularly in the community since the last known speaker, Sesostrie Youchigant, passed away in 1948. The center of the revitalization of the Tunica language is this first-of-its-kind, beginning Tunica language textbook. The Tunica Language Textbook (Rowinataworu Luhchi Yoroni) contains everything needed to be come conversationally fluent in Tunica. Like other language textbooks, it contains vocabulary and grammatical information, as well as practice exercises that develop both comprehension and production of Tunica, and acquisition of the patterns, not just the forms. The textbook contains links to an online pronunciation guide and includes a wealth of information on cultural topics, from stickball to basketry to naming to cosmology, and uses the language to do so. Wherever possible, excerpts from the original documentation of Tunica stories and myths have been included, so that students can become acquainted with native-like language use. Each chapter is structured to lead the student through the stages of learning, from presentation of new information, to recognition, to identification, to application. While there is explanation of the topics in English, the lessons are designed to be used in an immersion classroom setting as well as for individual use"--